Clinical outcomes and mortality in elderly peritoneal dialysis patients (Clinics, 2015)
OBJECTIVES: To evaluate the clinical outcomes and identify the predictors of mortality in elderly patients undergoing peritoneal dialysis. METHODS: We conducted a retrospective study including all incident peritoneal dialysis cases in patients ≥65 years of age treated from 2001 to 2014. Demographic and clinical data on the initiation of peritoneal dialysis and the clinical events during the study period were collected. Infectious complications were recorded. Overall and technique survival rates were analyzed. RESULTS: Fifty-eight patients who began peritoneal dialysis during the study period were considered for analysis, and 50 of these patients were included in the final analysis. Peritoneal dialysis exchanges were performed by another person for 65% of the patients, whereas 79.9% of patients preferred to perform the peritoneal dialysis themselves. Peritonitis and catheter exit site/tunnel infection incidences were 20.4±16.3 and 24.6±17.4 patient-months, respectively. During the follow-up period, 40 patients were withdrawn from peritoneal dialysis. Causes of death included peritonitis and/or sepsis (50%) and cardiovascular events (30%). The mean patient survival time was 38.9±4.3 months, and the survival rates were 78.8%, 66.8%, 50.9% and 19.5% at 1, 2, 3 and 4 years after peritoneal dialysis initiation, respectively. Advanced age, the presence of additional diseases, increased episodes of peritonitis, the use of continuous ambulatory peritoneal dialysis, and low albumin levels and daily urine volumes (